Комплексное исследование свиней по цито- и молекулярно-генетическим маркерам - Драгулян, М.В.; Костенко, С.А.; Сидоренко, Е.В. (Фактори експериментальної еволюції організмів, 2014)
Aim. The aim of this work was to identify and analyze the PRLR gene polymorphism and its association with reproductive qualities of sows Ukrainian meat and Welsh breeds as well as communication with the stability of genotypes animal genome. Methods. PRLR gene polymorphism analysis was performed by PCR – RFLP. To study the stability of the genome using the micronucleus test. Results. Ukrainian meat and Welsh breeds pigs mikropopulations were polymorphic by prolactin receptor gene (PRLR). A allele was associated with a greater number of born piglets and conservation. Animals, the desired allele carriers even elevated levels of white blood cells with micronuclei preserved high prolificacy. Animals BB genotype have a close negative correlation frequency of micro nucleated cells with multiple pregnancy. Conclusions. Lack of communication cytogenetic instability animal genotypes AA and AB with multiple pregnancy sow sindicatesthe presence in the reproductive system of compensatory mechanism sinvolvedin that prolactin receptor.

Key words: PRLR, prolactin receptor gene, the pig home, micronuclei, multiple pregnancy.